Pengaruh Likuiditas, Profitabilitas, Struktur Aktiva Dan Ukuran Perusahaan Terhadap Struktur Modal (Pada Perusahaan Otomotif Yang Terdaftar Di Bursa Efek Indonesia Tahun 2017-2019) - Fairoh Aida Qothrun Nada; Ronny Malavia Mardani; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study was conducted to examine whether the effect of the variables Liquidity, Profitability, Asset Structure, Firm Size on Capital Structure in Automotive Companies listed on the Indonesia Stock Exchange for the 2017-2019 period. In addition, to test the feasibility of the regression model for the influence of the variables Liquidity, Profitability, Asset Structure, Company Size on Capital Structure partially in Automotive Companies listed on the Indonesia Stock Exchange for the 2017-2019 Period. The population in this study is 13 automotive companies that have been and are still listed on the Indonesia Stock Exchange for the 2017-2019 period. The sampling technique used is purposive sampling and obtained as many as ten companies. The data analysis technique used is by using multiple linear regression tests. The results showed that Liquidity and Profitability had a negatif and significant effect on Capital Structure. Asset Structure and Firm Size variables have a positive and insignificant effect on Capital Structure. Keyword : Capital Structure, Liquidity, Profitability, Asset Structure, Firm Size